The Influence of Social Media on Teenagers' Lifestyles: Behavioral Analysis Among Adolescents in Bandung - Willya Achmad; Ade Sudrajat; Shinas Faiza; Reni Novita Ollianti (Departement of Mathematics Education, 2023)
Learning activities can be disrupted due to students' dependence on social media because more time is used to access social media than studying and to support the lifestyle of teenagers in general. This study aims to determine the effect of social media on the lifestyle of adolescents among young students in the city of Bandung. The method used is a survey with a simple random sampling technique. The results of the study show that the use of social media has a positive and significant influence on the lifestyle of adolescents in the city of Bandung by 43%. The practical implication of this research is the importance of socialization about the healthy and wise use of social media for adolescents.